Promoción turística basada en un sitio web para el desarrollo turístico del cantón Bolívar - Palma Cedeño, Ramón Wilfrido (2017)
The main objective of the present research was the design of a tourist promotion plan based on a website. In order to achieve the work, four phases were developed with their respective techniques and methods. The first phase was based on the search for bibliographic information regarding the design of online tourism promotion plans. In the second one, a situational diagnosis was elaborated in which the area of study was characterized and delimited, the tourist demand was analyzed; for this, a survey was conducted to the tourists, through which the importance and necessity to promote the tourism in the canton through a website was determined, in addition the profile of the visitor was identified; the existing tourist offer in the canton was established through a tourist inventory and the potential matrix, and a strategic analysis was carried out, in which the prevailing internal and external factors were defined. As a third phase, the tourist promotion plan was designed, which stipulated strategies, tactics and actions to promote a tourist destination based on the information available in the canton. In the last phase of the investigation, actions were taken to control and monitor the promotion plan.